How Speech–Language Pathologists Can Minimize Bullying of Children Who Stutter - Yaruss, J. Scott; Reeves, Nina; Herring, Caryn (Seminars in Speech and Language, 2018)
Stuttering can be a significant problem for children who stutter, but there is much that speech–language pathologists can do to help. This article summarizes six key steps, based on the work of Murphy and colleagues, that clinicians can take to minimize the occurrence and impact of bullying for children who stutter: (1) educating children about stuttering; (2) educating children about bullying; (3) helping children change the way they think and feel about their stuttering through desensitization, cognitive restructuring, and acceptance activities; (4) helping children learn to use appropriately assertive responses that decrease the likelihood of bullying; (5) educating peers and bystanders about stuttering and bullying so that they are more likely to respond in helpful ways; and (6) educating parents, teachers, and administrators about how they can create an environment where it is not okay to bully, but it is okay to stutter.
Keywords: Stuttering; communication disorders; therapy; bullying; treatment strategies